Physicochemical and microbiological properties of Kavılca Bulgur (A traditional cereal product of Turkey - ÇETİNKAYA, Asya; GÜLBAZ, Güven (Emirates Journal of Food and Agriculture, 2023)
Kavılca bulgur is a cereal product that is obtained from Kavılca wheat grown as a wheat type in Kars province and its surroundings. 40 unpackaged bulgur samples were used in this study and these samples were produced with traditional methods at family businesses under home conditions in Kars province and sold at delicatessens, grocery stores, and arcade marketplaces. In this study, which was carried out to determine the compliance of some microbial and physicochemical properties of Kavılca bulgur with the Turkish Food Codex Wheat Flour Communiqué and the Turkish Food Codex Microbiological Criteria Regulation, the samples were examined in terms of color, ash, moisture, pH, % titratable acidity (as sulfuric acid) and Total Aerobic Mesophilic Bacteria (TAMB), coliform, yeast-mold and rope-spore numbers Ash, moisture, and % titratable acidity ratios of Kavılca bulgur samples were found within the limits specified in the Turkish Food Codex Notification on Wheat Flour. According to the results of the microbiological analysis, the yeast-mold, coliform bacteria, and rope numbers were found to be within the range of the maximum acceptable limit stipulated in the Turkish Food Codex Regulation on Microbiological Criteria. We can say that it is important to develop and support the cultivation of Kavılca wheat, which has high nutritional value and can be utilized in various ways. Keywords: Bulgur; Kavılca; Microbial and physicochemical properties; Traditional cereal